A CRITICAL DISCOURSE ANALYSIS ON MEANING LEVELS IN HILLARY DIANE RODHAM CLINTON’S SPEECH ABOUT WOMEN - Ahmad Qomaruddin (Ulumuna: Jurnal Studi Keilsman, 2015)
This thesis examines the levels of meaning in Critical Discourse Analysis in the speech of Hillary Diane Rodham Clinton about women in the conference of World Summit in New York, the United State of America. This study aims at (1) finding the hidden ideology of Hillary Diane Rodham Clinton macrostructurally (global level of meanings), (2) meaning of words and propositions emphasized and controlled (local level of meanings), (3) and subtle of formal structures explicitly conveyed by her (pragmatic level of meanings). The descriptive qualitative design was used to analyze the data. Meanwhile, the theory used is Teun A. van Dijk’s Critical Discourse Analysis focused on the levels of meanings to help in analyzing the data. The data were taken from Hillary’s speech about women in the conference of World Summit in New York, the United State of America. The findings show that the hidden ideology of Hillary, in influencing the audiences, was expressed and delivered by emphasizing the importance of liberal or even radical feminism for increasing a better life of human beings. This can be known by using semantic macrostructural analysis. Then, the local meanings which focus on the words and proposition representing the ideology were used by her.  Instead, the formal structures were intentionally emphasized for controlling the speech. Thus, those three levels of Critical Discourse Analysis in investigating the meanings were eventually found in this research